Integrasi Gravity Model dan Indeks Kansky dalam Evaluasi Struktur Ruang Wilayah - Alfa Yoseph; Ari Wibowo; Susanto Susanto (Universitas Medan Area, 2026)
Regional connectivity is a fundamental aspect of spatial structure planning because it influences accessibility, spatial interaction among activity centers, and the efficiency of transportation systems. Subang Regency, one of the rapidly developing regions in West Java, has experienced significant economic growth and urban expansion, resulting in disparities in regional connectivity, increasing traffic volume, and suboptimal road network performance. This study aimed to evaluate the regional spatial structure of Subang Regency by integrating the Gravity Model and the Kansky Connectivity Index as a quantitative approach to identify the level of spatial interaction among activity centers and the quality of road network connectivity. A descriptive quantitative method was employed using secondary data, including population, inter-center distances, road network length, administrative area, and road network topology covering five Local Activity Centers (PKL) and twenty-four Area Service Centers (PPK). The analysis consisted of Gravity Model calculations to measure spatial interaction, road density analysis, and the Kansky Index (β) to assess road network connectivity. The integration of the Gravity Model and the Kansky Index provided a more comprehensive framework for evaluating regional spatial structure and could support infrastructure development priorities and sustainable regional planning in Subang Regency.